Protection of budding wounds in apple nursery trees from European canker - Scheper, R.W.A.; Stevenson, O.D.; Hedderley, D.I. (New Zealand Plant Protection, 2016)
The fungus Neonectria ditissima can cause European canker in apple nursery trees In this study ten treatments of EMLA 9 rootstocks budded with Royal Gala were examined 5 Treatments included combinations of five budding tapes two budding methods and three fungicidal treatments Fifteen months after inoculation all Tbudded trees had died Chipbudded trees inoculated after tying with either Flexiband type C or plastic precut strips displayed significantly more canker (21 and 22 respectively) than those tied with Buddy tape (11 P